(untitled) (Revista LIDER, 2021)
This work signals the current globalizad cultural situation as an area of execution of daily life, highlighting not only the need to know its interrelations, but also its expectations, for which it is situated at the level of the exigencies of interpretation that emanate from them. These exigencies are termed here, challenges.